2015
DOI: 10.1016/j.celrep.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural Constraints Determine the Glycosylation of HIV-1 Envelope Trimers

Abstract: A highly glycosylated, trimeric envelope glycoprotein (Env) mediates HIV-1 cell entry. The high density and heterogeneity of the glycans shield Env from recognition by the immune system but, paradoxically, many potent broadly neutralizing antibodies (bNAbs) recognize epitopes involving this glycan shield. To better understand Env glycosylation and its role in bNAb recognition, we characterized a soluble, cleaved recombinant trimer (BG505 SOSIP.664) that is a close structural and antigenic mimic of native Env. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
248
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 127 publications
(261 citation statements)
references
References 54 publications
(123 reference statements)
10
248
1
Order By: Relevance
“…Pal et al showed that gp41 from viruses prepared in MOLT-3 cells was Endo H resistant, but when prepared in the presence of an ER mannosidase inhibitor, 1-deoxymannojirimycin, gp41 became sensitive to Endo H digestion (59). More recent work by us and by Go and colleagues has shown that the gp41 glycans on recombinant gp140 trimers (13,60,61), including the SOSIP trimer (14), are predominantly complex type and that these structures are generally more dependent on producer cells. In this study, we were able to record the chromatograms of labeled glycans from PGT151-isolated pseudovirion-derived material and cell surface-associated Env to provide a more detailed description of glycan structures present on native virion-derived gp41.…”
Section: Oligomannose Isomers Are the Same On Pbmc-derived Env And Rementioning
confidence: 99%
See 4 more Smart Citations
“…Pal et al showed that gp41 from viruses prepared in MOLT-3 cells was Endo H resistant, but when prepared in the presence of an ER mannosidase inhibitor, 1-deoxymannojirimycin, gp41 became sensitive to Endo H digestion (59). More recent work by us and by Go and colleagues has shown that the gp41 glycans on recombinant gp140 trimers (13,60,61), including the SOSIP trimer (14), are predominantly complex type and that these structures are generally more dependent on producer cells. In this study, we were able to record the chromatograms of labeled glycans from PGT151-isolated pseudovirion-derived material and cell surface-associated Env to provide a more detailed description of glycan structures present on native virion-derived gp41.…”
Section: Oligomannose Isomers Are the Same On Pbmc-derived Env And Rementioning
confidence: 99%
“…cans, in particular Man 8 GlcNAc 2 and Man 9 GlcNAc 2 , forming the so-called IMP (14). These glycans are a key component of the epitope of the N332-dependent bnAbs (4,18,22).…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations